Successful hybridization between Clarias microstomus♂ and Clarias gariepinus♀ - Abit, Lirong Y. (Bioflux SRL, 2023)
Hybridization is a significant approach to breeding that enables the creation of new varieties that enhance genetic diversity. Through fish inter-species hybridization, it is possible to produce hybrids that can be utilized in aquaculture and stocking programs to enhance growth rate, transfer desirable traits between species, and combine the favourable attributes of two parents into a single progeny. The present study revealed the successful hybridization between Clarias microstomus (Ng, 2001) ♂ and Clarias gariepinus (Burchell, 1822) ♀ for the first time in the aquaculture industry. C. microstomus is a species of Clariid catfish endemic to the island of Borneo and C. gariepinus is an introduced species widely aquacultured throughout the southeast Asian region. The embryonic development of the hybrid offspring is described with the hatching percentage of 58.63 and the early survival rate for the first 72 hours for the larvae of 85.76. The hybrids showed no signs of deformities and developed normally. The findings of the study provide a new high yield variety of catfish for farmers and aquaculture industry for increasing production and profit margin.